2005
DOI: 10.1001/jama.294.18.2323
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Radiofrequency Ablation During Mitral Valve Surgery for Continuous Atrial Fibrillation

Abstract: Context Although left atrial radiofrequency ablation (RFA) is increasingly used for the treatment of chronic atrial fibrillation during mitral valve surgery, its efficacy to restore sinus rhythm and any resulting benefits have not been examined in the context of an adequately powered randomized trial. Objective To determine whether intraoperative RFA of the left atrium increases the long-term restoration of sinus rhythm and improves exercise capacity. Design, Setting, and Patients Randomized, double-blind tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 24 publications
3
123
0
1
Order By: Relevance
“…However, mortality and thromboembolic events during follow-up were low and similar in both groups. Doukas et al [18] in a randomized study of 97 patients found low efficacy of ablation (45% in one year), but it was possible to determine the benefits of maintaining sinus rhythm, especially the main and most functional capacity in walk test and smaller serum B-type natriuretic peptide. It was not possible to find differences in mortality or embolic complications during one year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, mortality and thromboembolic events during follow-up were low and similar in both groups. Doukas et al [18] in a randomized study of 97 patients found low efficacy of ablation (45% in one year), but it was possible to determine the benefits of maintaining sinus rhythm, especially the main and most functional capacity in walk test and smaller serum B-type natriuretic peptide. It was not possible to find differences in mortality or embolic complications during one year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…W następstwie zabiegu labiryntowania według Coxa wytworzony więc zostaje elektryczny labirynt (maze), w którym pobudzenie z węzła zatokowo-przedsionkowego znajduje drogę do węzła przedsionkowo-komorowego, a jednocześnie zapobiega się przewodzeniu migoczącemu. Zabieg labiryntowania według Coxa oraz inne, często prostsze, metody chirurgicznego leczenia AF wykonuje się głównie u pacjentów poddawanych innej operacji na otwartym sercu [461,466,[784][785][786][787][788][789][790][791][792][793][794][795][796][797][798]. W przeglądzie systematycznym zamówionym na potrzeby niniejszych wytycznych stwierdzono, że chirurgiczne leczenie AF przy okazji innej operacji kardiochirurgicznej zwiększało odsetek pacjentów bez AF, trzepotania przedsionków lub częstoskurczu przedsionkowego w porównaniu z niestosowaniem takiego leczenia (RR 1,94; 95% CI 1,51-2,49; n = 554 w 7 RCT) (dodatkowa ryc.…”
Section: Obserwacja Po Ablacji Przezcewnikowejunclassified
“…1290 Several other RCTs and meta-analyses are available to evaluate AF surgery at the time of concomitant mitral procedures. 1327,1328,1329,1330,1331,1332,1333,1334 Large LA, AF duration, advanced age, and failure to isolate the entire posterior LA are common predictors of reduced long-term efficacy. High baseline comorbid risk is a common reason cited for not performing surgical ablation, though many institutional studies note that this is not a contraindication to surgical ablation.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…Several recent RCTs and meta-analyses indicate that concomitant surgical ablation at the time of MVRR reduces the longitudinal incidence of postoperative AF greater than 50% for at least 1 year, with results ranging from 60%–90%. 1327,1328,1329,1330,1331,1333, 1334,1337,1338 In addition to LA size and preoperative AF duration, there is a procedural learning curve that can impact efficacy, and thus surgeons should seek appropriate training prior to performing surgical ablation.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%